What do we know about intratumoral functional activity: a scoping review of imaging and intra-surgery results - Ilaria Guarracino; Marta Maieron; Serena D’Agostini; Tamara Ius; Barbara Tomasino (NeuroImage: Clinical)
Intratumoral functional tissue represent a challenge in neurosurgery, as its resection may induce a permanent postoperative deficit. Only little is said in literature about this pattern. Currently this issue is receiving increased attention and in the last few years, the number of reports on intratumor functionality has increased. Aim of the current review was to provide a comprehensive overview of intratumoral area functionality patterns and of how much frequently this pattern is reported. PRISMA guidelines were followed. We identified 107 papers, but only 24 articles on 1220 patients were included for having reported intratumoral activation data. Within this framework, we aimed to shed light on some issues, including whether i) it is expressed only as fMRI activation within the mass, or whether it impacts on distant areas via functional connectivity, ii) it is found in slow growing tumors such as low grade glioma or also for fast infiltrative processes such as for high grade glioma, and iii) inhomogeneity of the tumor structure and morphological appearance or the tumor histology are key factors determining intratumoral area functionality. Key methods suitable for detecting intratumour function included MEG (in 7 studies), resting-state fMRI and task-active fMRI (in 8 studies) and intra-surgery direct cortical stimulation (in 8 studies). The type of patients were patients with astrocytoma (321 cases) and oligodendroglioma (255 cases) with tumor grade II (252 cases) and isocitrate dehydrogenase (IDH) mutation. Their mean tumor volume was 53.11 ± 19.23, and the affected hemisphere was mainly the left one (895 cases); lesion site most frequently involved the frontal cortex (435 cases). We discussed the clinical implications of these aspects, as a functional intratumoral area has a high impact on both planning and outcome, and we addressed the role of intra-surgery cognitive monitoring that should encompass a wide variety of functions.